Impact of antiphospholipid and antinuclear antibodies in coronary artery disease progression - Garcia-Camarero, Tamara; Martínez-Taboada, Víctor M.; Irure, Juan; Hernández, Jose M. de la Torre; Comins-Boo, Alejandra; López-Hoyos, Marcos; Hernández, José L. (Frontiers in Immunology, 2025)
Background/ObjectivesThe role of antiphospholipid (aPL) and antinuclear antibodies (ANA) in the progression of coronary artery disease (CAD) remains uncertain. We aimed to determine whether the presence of aPL or ANA predicts CAD progression.MethodsWe conducted a retrospective, single-center, case-control study including patients with CAD classified as either rapid clinical progressors (RCP) or long-standing stable (LSS), and a population-based control group. Autoantibodies analyzed included anticardiolipin (aCL), anti-β2 glycoprotein I (aB2GPI), anti-phosphatidylserine/prothrombin (anti-PS/PT), and ANA.ResultsWe included 180 CAD patients (58 RCP, 122 LSS) and 210 matched controls. CAD patients more frequently exhibited positive aCL (p<0.05), whereas aB2GPI IgA was higher among controls. The only significant difference between RCP and LSS was an increased prevalence of aCL IgA in RCP (p<0.05). No consistent differences were found in ANA positivity, antibody subtypes, or overall autoantibody load between groups.ConclusionsThis study does not support a significant role for aPL or ANA in the development or progression of CAD. These findings should be interpreted as hypothesis-generating, and larger, prospective multicenter studies with repeated antibody measurements are required to clarify these associations.